Neuroprotective effect of L-cycloprolylglycine on models neuronal cells damage in vitro - S. V. Nikolaev; I. O. Logvinov; P. I. Antipov; K. N. Kolyasnikova; T. A. Antipova (LLC "Publisher OKI", 2017)
We have studied neuroprotective effect of L-cycloprolylglycine (L-CPG) in vitro experiments. It is shown that L-CPG has neuroprotective effect in the conditions an oxidative stress, glutamate and 6-hydroxydopamine toxicity.